Low-cost power quality monitor based on a PC - Batista, José (2003)
This paper presents the development of a low cost digital system useful for power quality monitoring and power management. Voltage and current measurements are made through Hall-effect sensors connected to a standard data ac-quisition board, and the applications were programmed in LabVIEW™, running on Windows in a regular PC. The system acquires data continuously, and stores in files the events that result from anomalies detected in the monitored power system. Several parameters related to power quality and power man-agement can be analyzed through 6 different applications, named: “Scope and THD”, “Strip Chart”, “Wave Shape”, “Sags and Swells”, “Classical Values” and “p-q Theory”. The acquired information can be visualized in tables and/or in charts. It is also possible to generate reports in HTML format. These reports can be sent directly to a printer, embedded in other software applications, or accessed through the Internet, using a web browser. The potential of the developed system is shown, namely the advantages of virtual instrumentation, re-garding to flexibility, cost and performance, in the scope of power quality monitoring and power management.